2019
DOI: 10.1002/aur.2231
|View full text |Cite
|
Sign up to set email alerts
|

Differential profiles of response inhibition deficit between male children with autism spectrum disorders and schizophrenia

Abstract: Autism spectrum disorders (ASD) and schizophrenia (SZ) are both associated with response inhibition impairment. However, the relative pattern of deficits in these two disorders remains unclear. Twenty‐three male children with ASD, 23 male children with SZ, and 32 typically developing male controls were recruited to complete a set of tasks measuring response inhibition in the visual, auditory, and verbal domains. We found that visual, auditory, and verbal response inhibitions were impaired in both children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Within ASD, impaired response inhibition, a particular form of EF impairment, appeared in one small study to be associated with self‐reported “schizotypal” disorganized thoughts (Barneveld et al, 2013). This finding is interesting in light of a report of greater impairment in auditory response inhibition in SCZ compared to ASD in a population of males aged 11–16 but similar impairment in visual response inhibition across both disorders (Shi et al, 2020). Response inhibition may be a potential avenue for future exploration with regard to SCZ vulnerability within ASD.…”
Section: Resultsmentioning
confidence: 51%
“…Within ASD, impaired response inhibition, a particular form of EF impairment, appeared in one small study to be associated with self‐reported “schizotypal” disorganized thoughts (Barneveld et al, 2013). This finding is interesting in light of a report of greater impairment in auditory response inhibition in SCZ compared to ASD in a population of males aged 11–16 but similar impairment in visual response inhibition across both disorders (Shi et al, 2020). Response inhibition may be a potential avenue for future exploration with regard to SCZ vulnerability within ASD.…”
Section: Resultsmentioning
confidence: 51%
“…For instance, limitations and difficulties in inhibiting prepotent responses and suppressing distractors have been confirmed (for a review see Hlavatá et al, 2018;Zhang et al, 2020). Also, automatic inhibition of visual, auditory and verbal responses was found to be impaired in both ASD and SSD (Shi et al, 2020).…”
mentioning
confidence: 92%
“…( 21 ) found no differences between healthy controls and schizophrenic patients, Shi et al. ( 26 ) found no differences between ASD and SSD children, and Johnson et al. ( 22 ) found no differences between ASD and typically developing children.…”
Section: Discussionmentioning
confidence: 98%
“…While the lack of differences may be due to the SART being relatively an easy task to perform, these results partially overlap with findings from previous research, although caution is warranted since we are comparing our results to findings from populations with different diagnoses (schizophrenia) and at different developmental stages (children, elderly). With respect to commission errors on the fixed SART, O'Grada et al (19), Chan et al (20), and Ho et al (21) found no differences between healthy controls and schizophrenic patients, Shi et al (26) found no differences between ASD and SSD children, and Johnson et al (22) found no differences between ASD and typically developing children. In contrast, however, Johnson et al (22) reported higher number of commission errors in ASD relative to typically children while performing the random SART, and Geurts et al (23) reported similar results in elderly with ASD while performing the fixed SART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation